Performance evaluation of compound parabolic solar collector using different nanofluids: An experimental study - Farhan, Muhammad; Shahid, Muhammad Ihsan; Jamil, Furqan; Usman, Muhammad; Mujtaba, M. A.; Saleem, Muhammad Wajid; Nasir Shah, Syed; Saghir, Shahid; Yusuf, Abdulfatah Abdu; Mousa, Mohamed; El-Shafay, A.S. (Frontiers in Energy Research, 2022)
The paper reports an experimental study on a non-tracking compound parabolic collector (CPC) with hybrid nanofluids (NFs). An experimental setup was fabricated having concentration ratio of 4.17, 0.828m2 collector area, 24° of half acceptance angle, and evacuated tube receiver having 1.85 m length. Various fluids like water, NFs have been investigated in CPC performance improvement but still results are not satisfactory and thus current research deals with hybrid NFs in CPC. The 0.01% and 0.015% concentration were used of hybrid NFs which were silica/water+ethylene glycol (SiO2)/(H2O+EG), Magnesium oxide+carbon black/water (MgO+CB/H2O) and carbon black+Graphene Nanoplatelets/water (CB+GNPs/H2O) at flow rates of 0.02 kg/s,0.015 kg/s and 0.010 kg/s. The experimentation was performed under real climate conditions of Taxila, Pakistan and solar irradiance, ambient temperature were measured to determine the performance of CPC in comparison to simple base fluid which was water. The experimental results revealed that maximum temperature difference of 8.5°C with around thermal efficiency of 38.51% was achieved for hybrid pair of MgO+CB at flow rate of 0.01 kg/s and volumetric concentration of 0.015%. The efficiency variation using hybrid NFs of (SiO2 /EG+H2O) varies from 12.8% to 59.13% from lowest 0.01 kg/s to highest 0.02kg/s flow rates and volumetric concentrations (0.01% & 0.015%) of nano particles. For similar experimental conditions, efficiency variation for (CB+GNPs) pair varies from 14.2% to 65.68% for aforementioned conditions. Efficiency variation from 15.3% to 66.36% attained using MgO+CB in base fluid of water for said flowrates and volumetric concentrations of nano particles. In addition, an efficiency enhancement of 24.3%, 30.85%, and 31.53% was observed for SiO2/EG+H2O, CB+GNPs/H2O and MgO+CB/H2O respectively at maximum flowrates and volumetric concentration of nano particles as compared to water. Therefore, usage of hybrid NFs in CPC is beneficial in terms of efficiency enhancement and it will bring young researchers to get deep in this field to bring revolution in the area of solar energy.